PROPHET AL-KHIḌR: BETWEEN THE QUR’ANIC TEXT AND ISLAMIC CONTEXTS - Arnav Khobragade (Journal of Dharma, 2024)
Al-Khiḍr is the legendary figure mentioned in the Holy Qur’an (18:60-82) as a “servant of God.” Later Islamic scholars identify him as al-Khiḍr, "the Green One," implying that he brings vitality and growth to his surroundings, both metaphorically and literally. Irfan Omar’s book, Prophet al-Khiḍr aims to provide a comprehensive overview of the legacy of the Quranic al-Khiḍr, exploring the versatile roles he has assumed as his narrative evolved and intertwined with other legends, touching the hearts of millions throughout history.